2022
DOI: 10.1038/s42003-022-04005-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the fitness of a dual-antiviral drug resistant human influenza virus in the ferret model

Abstract: Influenza antivirals are important tools in our fight against annual influenza epidemics and future influenza pandemics. Combinations of antivirals may reduce the likelihood of drug resistance and improve clinical outcomes. Previously, two hospitalised immunocompromised influenza patients, who received a combination of a neuraminidase inhibitor and baloxavir marboxil, shed influenza viruses resistant to both drugs. Here-in, the replicative fitness of one of these A(H1N1)pdm09 virus isolates with dual resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Beyond individual patient benefit through mitigation of lethal infection and alleviation of viral pneumonia and lung immunopathogenesis, 4’-FlU statistically significant reduced upper respiratory tract virus load and viral shedding when treating 12 hours after infection, resulting in fully suppressed spread to untreated direct-contact sentinels in the highly sensitive ferret transmission model [ 50 ]. Later treatment initiation still reduced transmission efficiency, manifesting in delayed onset of virus replication and reduced upper respiratory tract peak virus load, which serves as a biomarker for risk of progression to severe viral pneumonia [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond individual patient benefit through mitigation of lethal infection and alleviation of viral pneumonia and lung immunopathogenesis, 4’-FlU statistically significant reduced upper respiratory tract virus load and viral shedding when treating 12 hours after infection, resulting in fully suppressed spread to untreated direct-contact sentinels in the highly sensitive ferret transmission model [ 50 ]. Later treatment initiation still reduced transmission efficiency, manifesting in delayed onset of virus replication and reduced upper respiratory tract peak virus load, which serves as a biomarker for risk of progression to severe viral pneumonia [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond individual patient benefit through mitigation of lethal infection and alleviation of viral pneumonia and lung immunopathogenesis, 4'-FlU statistically significant reduced upper respiratory tract virus load and viral shedding when treating 12 hours after infection, resulting in fully suppressed spread to untreated direct-contact sentinels in the highly sensitive ferret transmission model (49). Later treatment initiation still reduced transmission efficiency, resulting in delayed onset of virus replication and reduced upper respiratory tract peak virus load, which serves as a biomarker for risk of progression to severe viral pneumonia (50).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been concluded that resistance is largely due to the spread of a single variant [ 40 ]. Now, more than 10 years after this discovery, knowledge about not only the phenomenon of drug resistance, but also new anti-influenza drugs, vaccinations, or the genetics of the influenza virus itself, has significantly increased through the work of scientists and medical doctors [ 41 , 42 ]. Assessment of the susceptibility of currently circulating influenza viruses to antivirals is an important element of influenza virological surveillance required by the WHO, which the National Influenza Centers are trying to fulfill [ 43 ].…”
Section: Discussionmentioning
confidence: 99%